Educational Quality Management at Inpres Kema III Primary School - Tangkudung, Ernny Ningsy (Journal of Social Research, 2023)
This research aims to analyze and describe: the quality planning process, quality implementation, and quality evaluation at SD INpres Kema III, North Minahasa Regency. This research uses a naturalistic qualitative method, where data collection uses techniques: participant observation, interviews, and documentation studies. Based on the results of data analysis, it was concluded that 1) the process of improving the quality at SD Inpres Kema III went through stages: first, evaluation and analysis of the implementation of learning in the previous academic year by the principal, second, preparation of a quality improvement plan based on the results of the evaluation of the implementation of learning in the previous year, third, presentation of the evaluation results in the principal and the new quality improvement program plan at the meeting at the beginning of the school year (attended by the teacher council and school committee), the fourth discussion of the work program plan for the new school year, 2) quality implementation is by the quality improvement plan. In the process, the school principal acts as a "guardian" for the harmonization of organizational performance. This role is carried out in the form of 1) ensuring student security by ensuring that the fence is locked so that no one comes in and out without the principal's knowledge, 2) monitoring the presence of teachers in teaching, 3) ensuring the creation of education without violence (harmonious education), 4 ) motivator for teachers, 5) liaison between schools and parents/committees, 6) as a monitor for program implementation, 7) director when there is an imbalance in the implementation of activities, 8) counselor for teacher problems at school. Apart from the role of school principals and teachers, environmental support has a strategic role in improving the quality of SD Inpres Kema III. Groups that play a role include 1) government, 2) school committees, 3) Non-Governmental Organizations (NGOs), and 4) National Companies operating in North Minahasa Regency.